2022
DOI: 10.1093/burnst/tkac012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish oil-containing nutrition supplementation in adult sepsis patients: a systematic review and meta-analysis

Abstract: Background Sepsis is life-threatening organ dysfunction caused by a dysregulated host response to infection. Although fish oil has been used as an immunonutritional preparations for the treatment of sepsis patients, there is still controversy as to whether it is beneficial to them. We systematically reviewed published clinical trial data to evaluate the effectiveness of fish oil-containing nutrition supplementation in sepsis patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…99 A systematic review showed that parenteral nutrition containing fish oil, which is full of Ω-3 lipid, could significantly decrease mortality in sepsis patients. 100 In addition, Due to both energetic and metabolic consequences, mitochondrial dysfunction appears to play a significant role in the pathogenesis of sepsis. 101 This makes them a valuable subject for further research and a potential target for future therapies.…”
Section: Significance Of Metabolic Reprogramming In the Clinical Trea...mentioning
confidence: 99%
“…99 A systematic review showed that parenteral nutrition containing fish oil, which is full of Ω-3 lipid, could significantly decrease mortality in sepsis patients. 100 In addition, Due to both energetic and metabolic consequences, mitochondrial dysfunction appears to play a significant role in the pathogenesis of sepsis. 101 This makes them a valuable subject for further research and a potential target for future therapies.…”
Section: Significance Of Metabolic Reprogramming In the Clinical Trea...mentioning
confidence: 99%
“…Hereunder we review the data that might support this hypothesis. A number of meta-analyses of relevant trials of omega-3 PUFAs have been published recently [34 ▪ ,35 ▪ ,36,37]. Pradelli et al [34 ▪ ] reviewed 49 randomized controlled trials (RCTs) comparing omega-3 PUFA enriched PN with standard (nonomega-3 PUFA enriched) PN in adult hospitalized patients.…”
Section: Omega-3 Polyunsaturated Fatty Acids and Sepsismentioning
confidence: 99%
“…Omega-3 PUFAs were associated with lower mortality (RR 0.82, 95% CI 0.69, 0.97), shorter duration of mechanical ventilation (weight mean difference −2.20 days, 95% CI −4.00, −0.40), and shorter ICU LOS (weight mean difference −3.86 days, 95% CI −5.72, −2.01). Most recently, Wang et al [37] analyzed findings of 25 RCTs of enteral or parenteral provision of omega-3 PUFAs to patients with sepsis. They found that omega-3 PUFAs reduced mortality (RR 0.74, 95% CI 0.63, 0.86), and shortened duration of mechanical ventilation (weight mean difference −2.26 days, 95% CI −4.27, −0.26), ICU LOS (weight mean difference −3.57 days, 95% CI −4.54, −2.59) and hospital LOS (weight mean difference −9.92 days, 95% CI −15.37, −4.46).…”
Section: Omega-3 Polyunsaturated Fatty Acids and Sepsismentioning
confidence: 99%
“…Their potential role in elective surgery has been well documented: the benefits have also been supported by several very recent systematic reviews and meta-analyses, revealing a reduced risk of complications, lower length of hospital stays, and reduced mortality [ 3 , 4 , 5 ]. IN has shown its efficacy also in improving clinical outcomes in acute pancreatitis [ 6 ], critical illness [ 7 ], acute respiratory distress syndrome [ 8 ], and sepsis [ 9 ].…”
mentioning
confidence: 99%